2007
DOI: 10.1002/pola.22088
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of side‐on bisazobenzene‐containing homopolymers and block copolymers via ATRP and studies on their photoisomerization and photoalignment behaviors

Abstract: The preparation of a series of novel homopolymers and copolymers containing bisazobenzene chromophores with side‐on structure in the side chains via atom transfer radical polymerization (ATRP) were presented. UV–vis spectra of the thin films of these polymers under irradiation of 488 nm Ar+ laser suggested that the photoisomerization of the bisazobenzene chromophores happened mainly on one of the two azo groups in the bisazobenzene chromophores with similar probability due to their side‐on structure. Good phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…The lines are drawn to guide the eye. [4,10,24,35], copolymers [5,10,17,36,37] and blends [38,39] with the advantage of a relatively small writing time. The comparison of the two mixtures indicated that 41% molar fraction of azopolymer are sufficient for the photoinduced birefringence, with an optimized writing process using 1.4 mW of laser power.…”
Section: Tablementioning
confidence: 99%
“…The lines are drawn to guide the eye. [4,10,24,35], copolymers [5,10,17,36,37] and blends [38,39] with the advantage of a relatively small writing time. The comparison of the two mixtures indicated that 41% molar fraction of azopolymer are sufficient for the photoinduced birefringence, with an optimized writing process using 1.4 mW of laser power.…”
Section: Tablementioning
confidence: 99%
“…Firstly, an ATRP initiator with two specific functional groups (N-Ph) is prepared. Then, the precursor azo polymer with dianilino groups (P6OCN 16 ) is polymerized through ATRP with the obtained initiator. Finally, the Y-shaped amphiphilic azo triblock copolymer is obtained by the macromolecular azo-coupling reaction between P6OCN 16 and the diazonium salt of PEG 43 Figure 1 shows the 1 H NMR spectrum with resonance signal assignments of the newly synthesized ATRP initiator, which confirms that the ATRP initiator is successfully synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…38 16 ) CuBr (57.4 mg, 0.4 mmol) was added into a schlenk flask, and then the flask was degassed and back-filled with nitrogen for three times. After this step, deoxygenated ATRP initiator 3,5-bis(2-ethyl(phenyl)aminoethoxy)benzenemethyl 2-bromo-2-methyl-propionate (0.116 g, 0.2 mmol), azobenzene monomer 6-(4-cyano-azobenzene-4 0 -oxide)-hexyl methacrylate (6-OCN) (1.56 g, 4 mmol), 1,1,4,7,10,10-hexamethyl-triethylenetetramine (HMTETA) (110 lL, 0.4 mmol) and anisole (2.0 mL) were added.…”
Section: -(4-cyano-azobenzene-4mentioning
confidence: 99%
See 1 more Smart Citation
“…envisaged for these materials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It is now well established that the structural characteristics of block copolymer thin films can be controlled by manipulation of molecular weight, block volume fraction, and the interaction parameter, v. 1,4,5 In turn the orientation of the block domains in thin films is governed by boundary conditions such as commensurability and interfacial interaction between blocks and substrates. 1,4,5 In controlling the orientation of block copolymers in thin films, several strategies have been employed including surface modification, [17][18][19][20] solvent annealing, 21 electric fields, 22 graphoepitaxy, 23 chemical prepatterning, 24,25 shear, 26 etc.…”
Section: Introductionmentioning
confidence: 99%